THE PECULIARITIES OF THE FORMATION OF COMPLEX ADJECTIVES IN MODERN ENGLISH (Academicia Globe: Inderscience Research, 2023)
The article is devoted to the analysis of the peculiarities of the formation of complex adjectives in modern English, based on the concepts of well-known Germanists about word composition. As a result of the study, the most productive structural models of complex adjectives in the English language are identified.